2019
DOI: 10.32382/medkes.v14i2.749
|View full text |Cite
|
Sign up to set email alerts
|

Study of Correlation of Age and Parity of Mothers with Pre-Eclampsia in Pregnant Women in the Working Area of Mangasa Health Center in Makassar City

Abstract: Preeclampsia is the onset of hypertension with proteinuria due to pregnancy, after 20 weeks' gestation or immediately after delivery. These symptoms can occur before 20 weeks if trophoblastic disease occurs. This study aims to determine the relationship between age and maternal parity with the incidence of pre-eclampsia in pregnant women in the work area of the Puskesmas Mangasa, Makassar City. The research design used in this study was descriptive analytic research with a cross sectional study design. Conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…No significant age difference was observed between the study groups (p > 0.05) in this study. This finding was in line with the results of Yakub et al's study, which concluded that the age of pregnant women was not associated with the incidence of preeclampsia [29]. Ghafarzadeh et al also showed that Vitamin D levelsrelated preeclampsia did not significantly correlate with maternal age [30].…”
Section: Discussionsupporting
confidence: 87%
“…No significant age difference was observed between the study groups (p > 0.05) in this study. This finding was in line with the results of Yakub et al's study, which concluded that the age of pregnant women was not associated with the incidence of preeclampsia [29]. Ghafarzadeh et al also showed that Vitamin D levelsrelated preeclampsia did not significantly correlate with maternal age [30].…”
Section: Discussionsupporting
confidence: 87%